2009
DOI: 10.1002/adsc.200900481
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐Iron Oxide as a Recyclable Catalyst for Intramolecular CN Cross‐Coupling Reactions under Ligand‐Free Conditions: One‐Pot Synthesis of 1,4‐Dihydroquinoline Derivatives

Abstract: Abstract:The ligand-free nanoparticle ferroferric oxide catalytic system has been developed to promote the intramolecular C À N cross-coupling reaction. With this protocol, various 1,4-dihydroquinoline derivatives were synthesized from o-halobenz-A C H T U N G T R E N N U N G aldehydes and b-enaminones in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 100 publications
1
17
0
Order By: Relevance
“…Recyclability of the catalyst was tested upon the reaction of iodobenzene with phenylacetylene in ethylene glycol (EG). We observed that the catalytic activity of the catalyst was restored within the limits of the experimental errors for five successive runs as presented in Table 7, Very lately, such a restoration of catalytic activity for nanoparticles of Fe 3 O 4 has been also reported for the synthesis of α‐amino nitriles,18b propargylamines,18c and intramolecular CN cross‐coupling reactions 18d…”
Section: Resultssupporting
confidence: 65%
“…Recyclability of the catalyst was tested upon the reaction of iodobenzene with phenylacetylene in ethylene glycol (EG). We observed that the catalytic activity of the catalyst was restored within the limits of the experimental errors for five successive runs as presented in Table 7, Very lately, such a restoration of catalytic activity for nanoparticles of Fe 3 O 4 has been also reported for the synthesis of α‐amino nitriles,18b propargylamines,18c and intramolecular CN cross‐coupling reactions 18d…”
Section: Resultssupporting
confidence: 65%
“…20 Arylglyoxal monohydrate, as readily available 1,2-biacceptors 21 , can provide two active sites (C–O and C=O bonds), which can be attacked by the electron-rich β-C atom and NH group in β-enaminones for C–C and C–N bonds formation via [3+2] cyclization mechanism. We devoted our efforts on this study by using the reaction of 4-tolylglyoxal monohydrate 1a , a preformed 5,5-dimethyl-3-(4-bromophenylamino)cyclohex-2-enone 2a and 4-chlorobenzenamine 3a as the model reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[32,33] Semiconductive nanocrystals are attractive owing to their fluorescent properties. [34][35][36] Additionally, researchers have also observed the unique aspects of iron oxide nanoparticles, specifically their superparamagnetic [37][38][39][40] and catalytic [41,42] properties. Because of their small size, nanoparticles also exhibit a relatively large surface-tovolume ratio and quantum effects, that are substantially different from bulk materials.…”
Section: Nanoparticle Probes For Protein Detectionmentioning
confidence: 96%